2015
DOI: 10.1371/journal.pone.0129886
|View full text |Cite
|
Sign up to set email alerts
|

Plasma HIV-2 RNA According to CD4 Count Strata among HIV-2-Infected Adults in the IeDEA West Africa Collaboration

Abstract: BackgroundPlasma HIV-1 RNA monitoring is one of the standard tests for the management of HIV-1 infection. While HIV-1 RNA can be quantified using several commercial tests, no test has been commercialized for HIV-2 RNA quantification. We studied the relationship between plasma HIV-2 viral load (VL) and CD4 count in West African patients who were either receiving antiretroviral therapy (ART) or treatment-naïve.MethodA cross sectional survey was conducted among HIV-2-infected individuals followed in three countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
16
0
2
Order By: Relevance
“…of infants born to seropositive HIV-2 mothers, and for studying the HIV-2 reservoir. Plasma viremia is undetectable in many HIV-2-infected patients in the absence of antiretroviral therapy, particularly in those with high CD4 T cell counts (11). HIV-2 DNA may be the only detectable marker in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of infants born to seropositive HIV-2 mothers, and for studying the HIV-2 reservoir. Plasma viremia is undetectable in many HIV-2-infected patients in the absence of antiretroviral therapy, particularly in those with high CD4 T cell counts (11). HIV-2 DNA may be the only detectable marker in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the French National HIV-2 Cohort, 71% of antiretroviral-naive patients had plasma viral loads below 100 copies/ml (10). Data from a West Africa cohort showed that 46.5% of antiretroviral-naive patients had undetectable HIV-2 RNA (Ͻ10 copies/ml), and 35.8% had low HIV-2 RNA loads of 10 to 100 copies/ml (11). In this context, HIV-2 DNA may be the only detectable viral marker for patients with undetectable HIV-2 RNA.…”
mentioning
confidence: 99%
“…It has been shown in West Africa cohort study that 46.5% of HIV-2 infected patients were well controlling infection [21]. This seems due to a better immune response including better protection and less immunopathology [22].…”
Section: Discussionmentioning
confidence: 98%
“…As a reference comparative assay, we used an in-house qPCR based assay that is in current use at reference institutions in Portugal and other European countries (4,5,10,(38)(39)(40)(41)54). The associations between viral load and CD4 ϩ T cell counts or antiretroviral therapy status were similar for measurements obtained with ExaVir Load and qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…In HIV type 2 (HIV-2)-infected individuals, this evaluation is hindered by the inexistence of a "goldstandard" method for the quantification of HIV-2 viral load in the plasma. Unlike with HIV-1, for which there are commercial tests to quantify plasma viral load, specific quantification of plasma viral load in HIV-2-infected patients is only obtained through in-house assays developed for research use (4)(5)(6)(7)(8)(9)(10). This circumstance likely results from the low prevalence of HIV-2 infection worldwide.…”
mentioning
confidence: 99%